"Public Hospitals in Critical Condition": Death and Love as Embodied Care and Political Mobilization - Perray-Redslob, Ludivine (Business ethics quarterly, 2025)
This article examines how hospital workers engage in embodied mobilizations drawing on the life-affirming power of death and love to resist the demise of the French public hospital system. Drawing on Butler's work on "What is a livable life" (2022a, 2022b) and Notes toward a performative theory of assembly (2015), the study analyses a four-year data collection of Facebook posts, from two activist collectives of hospital workers. Our findings highlight three forms of ethical resistance. First, hospital workers mobilize the symbolism of death to denounce the erosion of public healthcare infrastructure and to urge the public to help save it. Second, they use this symbolism to shed light on the precariousness of their working conditions and to elicit compassionate care from citizens. Third, they make the symbolism of love for public healthcare visible, prompting reflection on the importance of public service values in a society rooted in solidarity and mutual care. This work contributes to the literature at the intersection of social mobilization and ethics of care: first, it brings to the front death and love as symbols that illuminate the radical political potential of care in social movements; second, it advances the theoretical construct of "ethics of publicness."